Revisiting the equity debate in COVID-19: ICU is no panacea. Issue 10 (22nd June 2020) - Ballantyne, Angela; Rogers, Wendy A; Entwistle, Vikki; Towns, Cindy
Abstract : Throughout March and April 2020, debate raged about how best to allocate limited intensive care unit (ICU) resources in the face of a growing COVID-19 pandemic. The debate was dominated by utility-based arguments for saving the most lives or life-years. These arguments were tempered by equity-based concerns that triage based solely on prognosis would exacerbate existing health inequities, leaving disadvantaged patients worse off. Central to this debate was the assumption that ICU admission is a valuable but scarce resource in the pandemic context. In this paper, we argue that the concern about achieving equity in ICU triage is problematic for two reasons. First, ICU can be futile and prolong or exacerbate suffering rather than ameliorate it. This may be especially true in patients with COVID-19 with emerging data showing that most who receive access to a ventilator will still die. There is no value in admitting patients with poor prognostic indicators to ICU to meet an equity target when intensive critical care is contrary to their best interests. Second, the focus on ICU admission shifts focus away from important aspects of COVID-19 care where there is greater opportunity for mitigating suffering and enhancing equitable care. We propose that the focus on equity concerns during the pandemic should broaden to include providing all people who need it with access to the highest possible standard of end-of-life care. This requires attention to culturally safe care in the following interlinked areas: palliative care, communication and decision support and advanced care planning.